2021
DOI: 10.2967/jnumed.121.262128
|View full text |Cite
|
Sign up to set email alerts
|

Slow but evident recovery from neocortical dysfunction and cognitive impairment in a series of chronic COVID-19 patients

Abstract: Cognitive impairment is a frequent complaint in coronavirus disease-19 and can be related to cortical hypometabolism on 18 F-FDG PET at the subacute stage. However it is unclear, if these changes are reversible. Methods: We prospectively assessed Montreal Cognitive Assessment (MoCA) and 18 F-FDG PET scans in 8 COVID-19 patients at the subacute (once no longer infectious) and chronic stages (approximately six months after symptom onset). The expression of the previously established COVID-19-related covariance … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
154
2
14

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(185 citation statements)
references
References 17 publications
15
154
2
14
Order By: Relevance
“…Particular impairments were found in attention [6][7][8][9][10][11][12] , memory [6][7][8][10][11][12][13] and executive functions. [10][11][12][14][15][16] More recently, using 18 F-FDG PET, it has been demonstrated that in the most severely affected patients, the degree of cognitive impairment was accompanied by frontoparietal hypometabolism. 10,11 Understandably, most of these small-scale reports have, to date, predominantly focused on symptomatic, hospitalised patients (however see 17 ).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Particular impairments were found in attention [6][7][8][9][10][11][12] , memory [6][7][8][10][11][12][13] and executive functions. [10][11][12][14][15][16] More recently, using 18 F-FDG PET, it has been demonstrated that in the most severely affected patients, the degree of cognitive impairment was accompanied by frontoparietal hypometabolism. 10,11 Understandably, most of these small-scale reports have, to date, predominantly focused on symptomatic, hospitalised patients (however see 17 ).…”
Section: Introductionmentioning
confidence: 99%
“…While many studies employ questionnaires reliant on patients' subjective self-reports, recent investigations have begun to document a wide range of post-COVID-19 cognitive deficits using objective cognitive testing of inpatients. Particular impairments were found in attention [6][7][8][9][10][11][12] , memory [6][7][8][10][11][12][13] and executive functions. [10][11][12][14][15][16] More recently, using 18 F-FDG PET, it has been demonstrated that in the most severely affected patients, the degree of cognitive impairment was accompanied by frontoparietal hypometabolism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“… Mittels der 18 FDG-PET (Fluordesoxyglukosepositronenemissionstomographie mit [ 18 F]) wurde bei 10 von 15 Long-COVID-Patienten mit neurokognitivem Defizit (weniger als 26/30 Punkte im MoCA[„Montreal cognitive assessment“]-Test) in frontoparietalen Hirnregionen ein Hypometabolismus nachgewiesen [ 5 ]. Beim Follow-up [ 2 ] von 8 Patienten über 6 Monate zeigte sich eine Symptomverbesserung mit weitgehender Normalisierung des Hirnstoffwechsels in der PET. Erfahrungen mit der SARS-1-Pandemie zeigten bereits, dass einzelne Patienten sehr lang anhaltende klinische Beschwerden zurückbehalten können, insbesondere Schmerzen, Fatigue, Depression und Schlafstörungen.…”
Section: Pathophysiologieunclassified
“…P-Werte wurden mittels 2-seitigen Fisher's-exact-Tests erhoben. während der Akutphase sind beschrieben und waren nach 6 Monaten teilweise rückläufig[15,16]. Mit der beschriebenen Basisdiagnostik können in vielen Fällen Long-COVID-Beschwerden nicht objektiviert und kausal erklärt werden.…”
unclassified